Requirements Elicitation in the Context of Software for Low-Functioning Autistic People: An Initial Proposal of Specific Supporting Artifacts - Melo, Aurea; Oran, Ana; Santos, Jonathas; Rivero, Luis; Barreto, Raimundo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2021: Anais do XXXV Simpósio Brasileiro de Engenharia de Software, 2021)
Requirements engineering is a crucial stage for the success of any software, as it allows a better understanding of the needs and desires of the customers or future users. In software development for autistic users, inexperienced software engineers face difficulties in the requirements engineering stage, as there are few specific techniques and artifacts to gather requirements in such context. The challenges increase when considering low-functioning autistic people, who have the most severe limitations of the disorder. Considering the above, in this paper, we present two artifacts to support the elicitation of requirements in software projects for autistic users. We developed a set of interviewing questions based on the opinion of both software development practitioners and caregivers. Also, we have drawn inspiration in a commercial canvas model to synthesize relevant data obtained with the interviews. When validating the artifacts, we got indicators of the feasibility of applying the artifacts in an actual development project. By developing and integrating these artifacts, we intend to support the requirements engineering stage and continue their development and study in further contexts.